An Integrated of AHP–QFD Methodology For Poduct Design: A Review - Rosnani Ginting; Aulia Ishak (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2020)
Many methods, rules, and techniques are used by some manufacturing companies to enhance product competitiveness by fulfilling customer needs and satisfaction possible by improving product design quality. Many researchers suggest a variety of design tools that were implemented early in the design process. Quality function deployment and Analytical hierarchy process methods are one of them. Some researchers have studied in-depth incorporating these two design techniques in product design and development by focusing on translating the consumers' desire into product design. This paper presents the review, investigates analysis, and discussion of some literature on the QFD combined AHP, which is used for product design, either re-designing existing products or designing new products. Several international journal articles have been selected, collected, and analyzed through several relevant scientific publications published in 2010-2016. An in-depth analysis has been carried out on this paper on the benefit, and drawbacks of the integration method on previous research. This paper provides suggestions based on the analysis of the development of the integration method. Hope this paper could be a reference for researchers and other manufacturing companies to implement QFD-AHP integration method in designing product